The Japanese community in the Philippines : before, during, and after the war - Osawa, Kiyoshi; Jugo-Nanagas, Marivi; editor; NTFI; translator (Manila : Joshu Bunko Library, 1994)
Originally published in Manila as "Yume no Hatemade Kinimukumamani" by Bysch Corporation
Keywords: Japanese in the PhilippinesOsawa, Kiyoshi-Authobiography.; Philippines -- History -- 1942-45 -- Personal narratives